Modern episteme, methodological nationalism and the politics of transnationalism - Jong, Abbas (Frontiers in Political Science, 2023)
Methodological nationalism can be understood in the broadest sense possible as any kind of correspondence between society and the unit of the nation-state. This equation can be traced and understood at two levels: firstly, within the socio-historical context of the rise of nationalism and the development of human and social sciences; and secondly, within the cognitive context of the emergence of nationalism and these sciences, or the modern episteme, in other words. By focusing on the latter, the present article aims to indicate that the problem of methodological nationalism can be effectively grasped by exploring the intricate interplay among modernity, the discourse of nationalism, and the emergence of social science, particularly concerning the modern episteme. It becomes apparent that the regime of foundationalist differentiation ingrained within the modern episteme has established the foundation for this correspondence or congruence—a regime that, while constructing determined, regulated, unified and completed categories, such as society and the social/nation-state and the national, simultaneously sets the ground for the exclusion of other non-social/non-national phenomena and events. In this paper, the objective is to demonstrate how, by disclosing the implementation of this regime as well as highlighting the contingent nature and, consequently, the conditions of the possibility of social phenomena in the path of their grounding, alongside prioritizing the indeterminate social configurations and arguing for a post-foundationalist approach and the politics of transnationalism, it becomes possible to overcome the problem of methodological nationalism. This, in turn, sets a basis for taking into account excluded and indeterminate phenomena and actors within a global context.